Understanding burnout in the HoReCa sector: The role of personal and work-related factors - Labus, Pero; Lukić Nikolić, Jelena (Hotel and Tourism Management, 2026)
Purpose – This study explores what causes burnout among employees in the HoReCa sector, focusing on how factors like gender, age, education, type of employment, and work experience relate to the three key aspects of burnout measured by the Maslach Burnout Inventory. Methodology – Data were collected through an anonymous online survey containing profile questions and items from the Maslach Burnout Inventory. The survey was shared by HoReCa managers in Serbia, Croatia, Montenegro, and Bosnia and Herzegovina, resulting in 1,234 completed responses between January and October 2024. The data were analyzed using IBM SPSS Statistics 26.0. Findings – The results indicate that factors such as age, type of employment, gender, education, and work experience all contribute to shaping burnout levels among employees in the HoReCa sector. However, age and employment type emerge as the most influential, while the effects of gender, education, and work experience appear to be more subtle. Implications – Burnout is a multifaceted condition, shaped by individual traits and specific work experiences. Tailored interventions, addressing the specific needs of employees based on their gender, age, education, type of employment and work experience, could help mitigate burnout and improve employee well-being and performance in the HoReCa sector.